Tasawuf dalam pemikiran Yusuf al-Qaradhawi (1926-2022) - Rabiatulasna Nassir,; Nozira Salleh, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Al-Qaradhawi is a contemporary Islamic scholar who is famous in the Islamic world. He is often used as a reference in solving various problems of Muslims, especially in the field of jurisprudence and da'wah. However, his expertise is not only focused on those two fields, but he is also knowledgeable in the field of Sufism. Therefore, this article tries to study al-Qaradhawi's views and thoughts about it, where he tried to purify the purity of Sufism and explain to the public the true concept of Islamic Sufism. Al-Qaradhawi asserted that what is required from the "pure rabbani life" is clarity of life's purpose, clarity of method, istiqamah in carrying out God's commandments, following the Sunnah of the Prophet S.A.W. as well as being in line with the manhaj of the Salafussoleh. The method of writing this article is based on literature research, by referring to books, journal articles, and materials related to the title. The result of the study clearly shows that al-Qaradhawi has a strong stance towards Sufism based on the Qur'an and Sunnah, so he strongly opposes heretical teachings and practices disguised as Sufism.